Production of single cell protein, essential amino acids, and xylanase by penicillium janthinellum - Rao, Mala; Varma, Anjanikumar; Deshmukh, Sumedha S. (Bioresources, 2010)
Microbial biomass having 46% crude protein content and enriched with essential amino acids as well as extracellular xylanase activity (100-150 IU/ml) was produced by an efficient fungal strain, Penicillium janthinellum (NCIM St-F-3b). Optimization studies for maximum xylanase and biomass production showed that the fungus required a simple medium containing bagasse hemicellulose as carbon source and ammonium sulphate as the nitrogen source. Therefore bagasse, which is a waste product of the sugar industry, can be efficiently used in microbioal biomass protein preparation for animal feed.
Keywords: Bagasse hydrolysate; Crude protein; Microbial biomass production; Penicillium janthinellum; Xylanase